Statistical characteristic measurements of propagation in durian orchard for sensor network at 5.8 GHz - Phaebua, Kittisak; Suwalak, Rattapong; Phongcharoenpanich, Chuwong; Krairiksh, Monai (My University, 2008)
The statistical characteristic measurement results of wireless sensor network in durian orchard at 5.8 GHz are presented. The measurement results are performed to study the channel characteristic of the radio wave propagation in the durian orchard. The communication channel is connected from sensor node to communication node and between communication node. The transmitter is setup at the bole of a durian tree for one communication node, and the received power by spectrum analyzer is used for the other communication node. Moreover, the transmitter is setup on the branch of durian tree for the sensor node placed on a durian. The signal strength is measured by spectrum analyzer. The sampling time of two seconds is employed to collect the signal strength for histogram plot. The statistical models, such as the Rican distribution and normal distribution are employed to fit the measurement results. These results can be used to approximate the statistical channel characteristics to predict the bit error rate in the wireless sensor network systems in durian orchard at 5.8 GHz. © 2008 IEEE.